Statistical evaluation of communication skills of customer care employees in banks - Korenková, Marcela (Business, Management and Economics Engineering, 2014)
The effectiveness of the sale of financial products in banks is largely influenced not only by the products themselves, but also by the level of communication skills of customer care assistants. The subject of our research was to find out the level of communication skills of customer care assistants in banks. The level of communication skills of customer care assistants considerably influences a suitable selection of employees for a position of a customer care assistant in the companies providing the bank products. They are also some supporting activities that the company itself uses to invest into the development of the assistant by the means of additional education, trainings and supporting activities. The research was realized in the banks operating in Slovakia and the collected data were analysed by the means of statistical methods that enabled us to identify the differences among individual banks. The results of our research prove that the communication skills of customer care assistants are at a sufficient level. Banks started to focus more on the increase of the level of provided services, too, in relation to the high competitiveness and the need to bring something more to a client.